ANALISIS EFEKTIVITAS KOMUNIKASI GOOGLE CLASSROOM SEBAGAI MEDIA PEMBELAJARAN ONLINE TERHADAP PRESTASI BELAJAR MAHASISWA FMIPA UNIVERSITAS RIAU - Monita, Ristara; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
use of Google Classroom online learning media is not a new thing to be used in supporting lecture activities. This learning media is also an alternative that is used to support learning that is complementary not to replace direct learning. According to the CMC (Computer Mediated Communication) theory, the CMC pattern allows a person to communicate using computer-based communication tools or gadgets supported by internet devices and applications that allow us to virtually do various activities such as discussing, reading, watching and accessing the required sites .The method used in this research is to use quantitative research methods, and the type of research approach used is causal research. The sampling technique used was purposive sampling of 93 respondents or active students of the Faculty of Mathematics and Natural Sciences, University of Riau, the number of respondents was obtained through the Slovin formula. The data analysis method used is simple linear regression, t test, and testing the coefficient of determination.The results of this study indicate that there is a significant influence between the effectiveness of communication on learning achievement for the students of the Faculty of Mathematics and Natural Sciences. Google Classroom as an online learning media for FMIPA UNRI students shows the effectiveness of communication seen from the optimization of the media used in supporting learning processes and activities on campus, and can also be seen in the learning achievements of FMIPA students which show intellectual factors including cognitive, affective and the psychomotor.Â Keywords : Google Classroom, Online Learning Media, Learning Achievement